Conference report (including non-peer reviewed articles) from the 14th Nordic Conference on Reindeer and Reindeer Husbandry Research, 20-22 March 2006, Vantaa, Finland - Haugerud (Editor), Rolf Egil (Rangifer, 2007)
The 14th Nordic Conference on Reindeer and Reindeer Husbandry Research Den 14. nordiske forskningskonferansen om rein og reindrift Vantaa, Finland, 20.-22. mars 2006Complete conference report, see Full text